PENGEMBANGAN VIDEO ANIMASI PERSONAL HYGIENE MENSTRUATION PADA REMAJA PUTRI PONDOK PESANTREN SALAFIYAH KHAIRA UMMAH SUMEDANG (Politeknik Kesehatan Kemenkes Bandung, 2023)
Personal Hygiene Menstruation is one that is very important for adolescent girls duringmenstruation to maintain and maintain personal hygiene, especially in the area of ​​​​thereproductive organs. Based on data from the Ministry of Health (2017)it shows that 5,2milion adolescent girls often experience complaints after menstruation due to notmaintainining personal hygiene, namely pruritus vulvae. Increased knowledge can bedone through education using interactive media, one of which is animated video media.Animated video media was chosen because it facilitates the delivery of information,combines audio and visual, and can attract the attention of teenagers. The purpose ofthis research is to develop an animated video media about personal hygienemenstruation that is appropriate and attractive as a tool for health education for youngwomen at the Salafiyah Khaira Ummah Islamic Boarding School, Sumedang Regency.This research is a development research (Research and Development) with theapproach model used is ADDIE. The sample in this study was 31 students of theSalafiyah Khaira Ummah Islamic Boarding School, Sumedang Regency, which wereselected using purposive sampling technique. The results showed that the mediafeasibility test by material experts got a score of 100% and by media experts it got ascore of 75%, and from the small group test it got a value of 95%. Recommendations:personal hygiene menstruation animation video media that has been developed andcan be applied in everyday life, further research can be carried out to determine theeffectiveness of the media and can develop this animated video media as a personalhygiene menstruation educational media program based on a health promotionstrategy.